Factors Influencing Customer Switching Intentions in Online Food Delivery: A Perspective of The Push-Pull-Mooring Model - Raden Ayu Nurlinda; Chairul Anam (Institute of Research and Community Outreach - Petra Christian University, 2024)
The online food delivery applications born in the digital era have transformed the habits of users in meeting their needs through these platforms. With the convenience of ordering various cuisines from the comfort of their homes, customers experience significant time and energy savings. In this context, service providers must deliver acceptable service quality; otherwise, customers will swiftly switch to competitors offering better value. This research aims to identify the driving, pulling, and anchoring effects on the intention of customers to switch between online food delivery services, utilizing the Push-Pull-Mooring framework to evaluate the relationships between variables. The study employed Structural Equation Modeling of the Partial Least Squares (SEM-PLS) type. The research findings indicate that push effects and pull effects have a positive influence on switching intention, while mooring effects do not positively impact switching intention. Furthermore, the study reveals that mooring effects do not moderate the relationship between push effects, pull effects, and switching intention. These evaluation results can serve as guidance for online food delivery companies, assisting them in enhancing their services to build strong relationships with existing customers and attract new ones.